Emodin Protects Sepsis Associated Damage to the Intestinal Mucosal Barrier Through the VDR/ Nrf2 /HO-1 Pathway - Shang, Luorui; Liu, Yuhan; Li, Jinxiao; Pan, Guangtao; Zhou, Fangyuan; Yang, Shenglan (Frontiers in Pharmacology, 2021)
Abstract Aims: Emodin is an anthraquinone extracted from Polygonum multiflorum, which has potential anti-inflammatory and anti-oxidative stress effects. However, the possible protective mechanism of emodin is unclear. The purpose of this study was to investigate the protective mechanism of emodin against cecal ligation and puncture and LPS- induced intestinal mucosal barrier injury through the VDR/ Nrf2 /HO-1 signaling pathway. Methods: We established a mouse model of sepsis by cecal ligation and puncture (CLP), and stimulated normal intestinal epithelial cells with lipopolysaccharide (LPS). VDR in cellswas down-regulated by small interfering ribonucleic acid (siRNA) technology.Mice were perfused with VDR antagonists ZK168281 to reduce VDR expression and mRNA and protein levels of VDR and downstream molecules were detected in cells and tissue. Inflammation markers (tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6)) and oxidative stress markers (superoxide dismutase (SOD), malondialdehyde (MDA) and glutathione (GSH)) were measured in serum and intestinal tissueby enzym-linked immunosorbent assay. The expression of VDR in intestinal tissue was detected by immunofluorescence. Histopathological changes were assessed by hematoxylin and eosin staining. Results: In NCM460 cells and animal models, emodin increased mRNA and protein expression of VDR and its downstream molecules. In addition, emodin could inhibit the expressions of TNF-α, IL-6 and MDA in serum and tissue, and increase the levels of SOD and GSH. The protective effect of emodin was confirmed in NCM460 cells and mice, where VDR was suppressed. In addition, emodin could alleviate the histopathological damage of intestinal mucosal barrier caused by cecal ligation and puncture. Conclusion: Emodin has a good protective effect against sepsis related intestinal mucosal barrier injury, possibly through the VDR/ Nrf2 /HO-1 pathway.